2010
DOI: 10.1051/epjconf/20100211003
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of deuteron breakup reactions for energies up to 100 MeV

Abstract: Abstract. Inclusive nucleon spectra from deuteron breakup reactions on 7 Li and 12 C up to 100 MeV are analyzed by using the continuum discretized coupled channels theory for elastic breakup process and the Glauber model for nucleon stripping process. The preequilibrium and evaporation components are estimated phenomenologically in terms of the moving source model. The calculation reproduces a prominent bump observed around half the incident energy in experimental inclusive spectra at forward angles quite well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…The LBNL 88-Inch Cyclotron is capable of accelerating deuterons up to a maximum energy of 65 MeV with maximum currents on the order of 10 μA [27]. Deuterons, with a neutron separation energy of 2.22 MeV, are weakly bound and will produce neutrons via breakup in the Coulombic field of a heavier nucleus (elastic breakup), proton stripping reactions (inelastic breakup), and pre-equilibrium and evaporation emission from the excited compound nucleus formed by deuteron absorption [28][29][30][31]. Each production mechanism produces neutrons with different angular and energy distributions.…”
Section: Beam Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The LBNL 88-Inch Cyclotron is capable of accelerating deuterons up to a maximum energy of 65 MeV with maximum currents on the order of 10 μA [27]. Deuterons, with a neutron separation energy of 2.22 MeV, are weakly bound and will produce neutrons via breakup in the Coulombic field of a heavier nucleus (elastic breakup), proton stripping reactions (inelastic breakup), and pre-equilibrium and evaporation emission from the excited compound nucleus formed by deuteron absorption [28][29][30][31]. Each production mechanism produces neutrons with different angular and energy distributions.…”
Section: Beam Designmentioning
confidence: 99%
“…The neutron distribution is narrows with increasing due to the higher ∕ of the heavier target nucleus and the increasing relative fraction of the elastic channels [29,32,33]. In contrast, the pre-equilibrium and evaporative emission channels will be roughly isotropic and have energy distributions peaked at much lower energies based on the characteristic temperature of the nucleus [31,33,34]. As the neutron emission angle increases, the relative contribution of the pre-equilibrium and evaporative emission channels increase, and the resulting energy distribution is far broader and less intense [31][32][33]35].…”
Section: Beam Designmentioning
confidence: 99%
“…Deuteron interactions with nuclei at energies below ∼200 MeV remain a topic of ongoing research [1][2][3][4][5], with eminent practical interest, among other as sources of mostly forward-scattered neutrons and protons, leading to a variety of applications in detector technology, accelerator shielding design, etc. Unfortunately, the inclusion of deuteron interactions in a general-purpose Monte-Carlo code for the simulation of radiation transport is not straightforward due to the idiosyncrasies of the deuteron: its low binding energy and the predominantly direct nature of its interactions with target nuclei in the considered energy domain make it not directly amenable to treatment with customary statistical (intranuclear cascade) models.…”
Section: Introductionmentioning
confidence: 99%
“…As for the analyses of the (d,xp) and (d,xn) reactions, Ye et al [16,17] once suggested a microscopic approach with the CDCC method for the EB process and the Glauber model [18] for the stripping process. This approach reproduced well the experimental data of DDXs at forward angles for several targets at energy up to 100 MeV.…”
mentioning
confidence: 99%
“…It was applied successfully for the deuteron induced elastic breakup reaction. [11,12,16,17,25] The three-body transition matrix of (d,np) reaction can be deduced from the CDCC equation and the boundary conditions. Then, the DDX of elastic breakup proton emission is written as Eq.…”
mentioning
confidence: 99%